Comparación del injerto gingival libre y el injerto submucoso de tejido conectivo para el cubrimiento de recesiones marginales gingivales - Arango-H., Gloria Nancy; Latorre-C., Federico (Revista Facultad de Odontología Universidad de Antioquia, 2020)
This clinical study was designed to determine which technique would result in more predictability for covering marginal tissue recession, the connective tissue graft (CTG), or thick free gingival graft (FGG) Eighteen surgeries were made on five patients with bilateral recessions, nine of them with FGG treatment and the other nine with CTG treatment, those patients had a mean of age of 34.5 year and a good oral health. Root coverage, clinical level of attachment, periodontal esthetic, tetracycline (HCL) use and post surgical discomfort were evaluated. Additionally a periodontal esthetic index was design. Both procedures didn’t showed significant statistical differences on basis of percentage of root coverage, with a P=0.0719. FGG treatment covered 52.3% and CTG a 67.9% of the marginal tissue recession. In both treatments showed an attachment level gain, with a significant difference and a P=0.00. A significant difference was seen when periodontal esthetic were compared, with a P=0.0117 showing a good and excellent behavior for CTG (88.9%) and good for FGG (22.2%). This study has proved that the palate is a painful site and FGG is a more painful surgery. In fact CTG treatment show a better clinical behavior than FGG and that tetracycline does not represent additional benefits.